2022
DOI: 10.9734/jpri/2022/v34i25b35962
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices (KAP) Study on Diabetic Foot Care among Diabetic Patients with Diabetic Foot Lesions in District Bahawalpur, Pakistan

Abstract: Diabetes mellitus is a chronic multifactorial metabolic illness that is characterized by numerous chronic complications. Diabetes affects almost every system of the body. Among these diabetic foot is one of the major complications of diabetes mellitus. Its main objective was to investigate the knowledge, attitude and foot care practices in diabetic patients suffering from diabetic foot lesions. An institutional-based cross-sectional study was designed to be conducted at Civil Hospital, Bahawalpur, Pakistan. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similarly, an across-sectional study on diabetes patients' knowledge, attitudes, and behavior regarding diabetic nephropathy, neuropathy, and retinopathy (Dia et al, 2022) conducted in Lebanon revealed that the prevalence of type II diabetes and type I diabetes was 82.23% and 15.65%, respectively. Yet another institutional cross-sectional study carried out in Pakistan found that the prevalence of type II and type I diabetes was 91.3% and 8.66%, respectively (Shamim et al, 2022). According to a report from the most recent research done in the United States, diabetic neuropathy affects between 6 and 51% of the diabetic population.…”
Section: Food Frequency Of Adult Patients Diagnosed With Diabetes Neu...mentioning
confidence: 99%
“…Similarly, an across-sectional study on diabetes patients' knowledge, attitudes, and behavior regarding diabetic nephropathy, neuropathy, and retinopathy (Dia et al, 2022) conducted in Lebanon revealed that the prevalence of type II diabetes and type I diabetes was 82.23% and 15.65%, respectively. Yet another institutional cross-sectional study carried out in Pakistan found that the prevalence of type II and type I diabetes was 91.3% and 8.66%, respectively (Shamim et al, 2022). According to a report from the most recent research done in the United States, diabetic neuropathy affects between 6 and 51% of the diabetic population.…”
Section: Food Frequency Of Adult Patients Diagnosed With Diabetes Neu...mentioning
confidence: 99%